Test of low-dropout voltage regulators with neutrons and protons. (1st May 2022) - Abovyan, S.; Bianchi, B.; Cesaroni, M.; Corradi, M.; Danielyan, V.; Falconi, L.; Ferraro, R.; Fras, M.; Gkountoumis, P.; Kortner, O.; Kroha, H.; Longarini, I.; et al.
Abstract: The Muon System of the ATLAS experiment at the CERN LHC will be upgraded for the high-luminosity phase of LHC to cope with higher rates and higher radiation levels. Most of the Muon-System on-detector electronics will be replaced. Commercial low-dropout voltage regulators have been considered as a robust, low-noise and economic solution to power distribution. These components should be selected based on their capability to comply to radiation requirements. We tested 7 different types of CMOS LDOs, monitoring online the output voltage of 10 samples of each type. Irradiations were performed in the Radial Channel 1 of the RSV TAPIRO fast neutron reactor at ENEA Casaccia (Rome), to test resistance to non-ionizing energy loss, and at the PIF 200 MeV proton beam at PSI (Villigen), to test for total ionizing dose and single event effects. The experimental setup and the results are presented and discussed in this paper.